ASSESSMENT OF THE LINK BETWEEN MACROECONOMIC DEVELOPMENT INDICATORS AND TAX REVENUES OF THE COUNTRY - Burunowa Оlena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In any country, the tax system acts as the basis of the economic system. In Poland, the process of improving the tax system is constantly underway. It is aimed at unification with world norms and standards and depends on the strategic directions of the national economic development. Since the opportunities for implementation of the country's strategic development programmes depend on the level of the state income and the main indicators of national development are macroeconomic indicators, the purpose of the paper is to study the relationship between the dynamics of macroeconomic indicators and tax revenues of the country. In the research study there were used some general scientific and special methods, such as: systematic method (in the research study of taxes in the structure of budget revenues); comparison, grouping, analysis and synthesis, statistical method (in analysing the dynamics of macroeconomic indicators and the volume of tax revenues in the budget of Poland); method of logical generalisation (for the formation of conclusions). The research used data exclusively from the official statistical sources of the Main Statistics Office of Poland, the National Bank of Poland, the Ministry of Finance of Poland. The paper identifies the importance of tax revenues in the revenue part of the budget, analyzes the growth rates of taxes and macroeconomic indicators, establishes a correlation and a regression relationship between gross domestic product, public debt, balance of trade, volume of gold reserves and total tax revenues, and also outlines the level of efficiency of the Polish tax system on the basis of the coefficient of tax elasticity. The results of the research study showed that tax revenues are sensitive to changes in the growth of gross domestic product, as well as changes in public debt, exports and imports, gold and foreign exchange reserves. All the above should take into account the country while being in the budget planning and forecasting process.